An experimental investigation of the draw resonance in film casting of polypropylene melts - Grieß, Hans Jürgen; Münstedt, Helmut; Burghelea, Teodor; Schubert, Dirk W. (Book of Abstracts, 2012)

An in situ investigation of the draw resonance phenomenon in film casting of a polypropylene melt - Burghelea, Teodor I.; Grieß, Hans Jürgen; Münstedt, Helmut (Journal of Non-Newtonian Fluid Mechanics, 2012)
An experimental investigation of the stability of the casting process of a polypropylene film is presented. By combined in situ measurements of the width of the cast film and Digital Particle Image Velocimetry (DPIV) measurements of the velocity distributions within the polymer film, several flow regimes are identified: stable, oscillatory and chaotic. Measurements of the velocity distribution along and across the extruded film corresponding to each drawing regime are presented. The intermittent physical rupture of the film's edges observed within the chaotic drawing regime is explained by the emergence of a " V-shaped" region of high axial gradients of the axial velocity component which indicates a highly inhomogeneous distribution of tensile stresses.By measurements of the statistics of the fluctuations of both the film's width and velocity a continuous (second order) imperfect bifurcation towards oscillatory states is found. The fluctuation data acquired before the chaotic regime is reached can be fitted by the stationary Landau-Ginsburg equation. The observation of a stable limit cycle at the onset of the bifurcation identifies it as a supercritical Hopf bifurcation. The experimentally found scaling of the onset and amplitude of the bifurcation with the Weissenberg number indicates that elasticity destabilizes the drawing process. This can be explained by the thinning behavior of the material in both shear and extension.The spectral analysis of the fluctuations of both film's width and point-wise velocity provides a quantitative description of the harmonics excited beyond the bifurcation point. The transition to chaotic states is accompanied by a major reorganization of the power spectra consistent with a period doubling bifurcation of a stable limit cycle. © 2012 Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Chaos; Coat hanger die; Draw resonance; Film casting; Imperfect bifurcation

A novel chip-based parallel transfection assay to evaluate paracrine cell interactions - Kühn, Elisabeth; Naschberger, Elisabeth; Konrad, Andreas; Croner, Roland S.; Britzen-Laurent, Nathalie; Jochmann, Ramona; Münstedt, Helmut; Stürzl, Michael (Lab on A Chip, 2012)
Created from Fastlane, Scopus look-up

Artefacts of the storage modulus due to bubbles in polymeric fluids - Wolff, Friedrich; Münstedt, Helmut (Rheologica Acta, 2013)
The occurrence of bubbles in samples to be characterised by rotational rheometry may lead to artefacts which can easily be misinterpreted. Exemplarily, a silicone resin is discussed which shows the formation of small bubbles near the interphase between the sample and the rheometer plate if the samples are not carefully dried before being installed in the rheometer. These small bubbles which can easily be overlooked lead to a bending of G′ at low frequencies which was erroneously attributed to the molecular structure in the past. Therefore, even for hydrophobic polymers like the silicone resin, great care concerning bubbles has to be taken since water might be adsorbed on the surface and lead to artefacts which result in wrong conclusions. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up
Keywords: Bubbles; Frequency dependence; Humidity; Silicone resin; Storage modulus

Behaviour of conductive particle networks in polymer melts under deformation - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W.; Münstedt, Helmut (AIP Conference Proceedings, 2011)
The electrical properties of the composites containing conductive fillers are given by the structure of the particle network. Therefore, the behavior of these networks under deformation in the molten state is of great interest in order to obtain materials with desirable electrical properties. In this work the composites containing carbon black or carbon fibers were exposed to a shear deformation in two different experimental modes—oscillation and creep and the electrical conductivity of the materials was measured simultaneousl
Keywords: Polymer composites; Conductivity; Rheology

Behaviour of conductive particle networks in polymer melts under deformation - Stary, Zdenek; Krückel, Johannes; Schubert, Dirk W.; Münstedt, Helmut (Novel Trends In Rheology IV, 2011)
Keywords: Polymer composites; Conductivity; Rheology

Cellular Metals and Polymers - Singer, Robert; Körner, Carolin; Altstädt, Volker; Münstedt, Helmut (Trans Tech Publications LTD, 2005)

CO2-laser treatment of indium tin oxide nanoparticle coatings on flexible polyethyleneterephthalate substrates - Königer, Tobias; Rechtenwald, Thomas; Al-Naimi, Ihab; Frick, Thomas; Schmidt, Michael; Münstedt, Helmut (Journal of Coatings Technology and Research, 2010)
A CO2-laser treatment was used to improve the electrical conductivity of coatings of indium tin oxide (ITO) nanoparticles on flexible polyethyleneterephthalate (PET) substrates. The electrical conductivity and the transparency of CO2-laser-treated ITO nanoparticle coatings were characterized with regard to the application as transparent electrodes. Furthermore, the stability of the electrical conductivity under oscillatory bending was investigated. A specific resistance of 0.12 Ω cm is obtained by CO2-laser treatment without thermally damaging the PET film. The improvement of the electrical conductivity can be explained by a slight sinter neck formation. For a film thickness of 3 μm, a sheet resistance of 400 Ω/□ and a transmission in the visible range of 80%were achieved. The stability of the electrical conductivity of CO2-laser-treated ITO nanoparticle coatings under bending was investigated using a specially constructed device for the application of various oscillatory bending loads. For a bending radius of 10 mm, the sheet resistance does not exceed 1000 Ω/h after 300 bending cycles. Compared to commercial sputtered ITO coatings, CO 2-laser-treated ITO nanoparticle coatings show a significant higher stability under oscillatory bending. © FSCT and OCCA 2009.
Created from Fastlane, Scopus look-up
Keywords: Indium tin oxide (ITO); Laser treatment; Nanoparticles; Oscillatory bending tests

Comparison of rheological and electrical properties of polymethylmethacrylate filled with carbon black or carbon fibres - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W.; Münstedt, Helmut (Final Program and Book of Abstracts, 2011)

Comparison of viscous and elastic properties of polyolefin melts in shear and elongation - Wolff, Friederich; Resch, Julia; Kaschta, Joachim; Münstedt, Helmut (Rheologica Acta, 2010)
Viscous and elastic properties of a linear polypropylene (PP) and a long-chain branched low-density polyethylene (LDPE) have been investigated by creep and creep-recovery experiments in shear and elongation. The data obtained verify the ratios between the linear values of the viscosities and the steady-state elastic compliances in shear and elongation predicted by the theory of linear viscoelasticity. In the nonlinear range, no simple correlation between the viscous behaviour in shear and elongation exists. The elongational viscosity of the PP decreases with increasing stress analogously to the shear thinning observed; the linear range extends to higher stresses in elongation than in shear, however. The LDPE shows thinning in shear and strain hardening in elongational flow. For the LDPE, a linear steady-state elastic tensile compliance corresponding to one third of the linear steady-state elastic compliance in shear was determined. For the PP, this theoretically predicted value is approximately reached. Analogous to the viscous behaviour, the linear range extends to higher stresses in elongation than in shear. For both materials, the steady-state elastic compliances in the nonlinear range decrease with increasing stress in shear as well as in elongation. However, the decrease in elongation is more pronounced.
Keywords: Polypropylene; Polyethylene; Viscosity; Elasticity; Shear; Elongation

Compression moduli of foamed films of fluorinated ethylene propylene copolymers determined by nanoindentation - Zirkel, Larissa; Maier, Verena; Durst, Karsten; Münstedt, Helmut (Polymer Testing, 2011)
Nanoindentation was applied to determine the elastic moduli in the compression mode of films of fluorinated ethylene propylene copolymers (FEP) foamed by means of supercritical carbon dioxide. For this purpose, a flat punch indenter with a diameter larger than the average cell size of the foams was found to be appropriate. The dependence of the mechanical properties of the films on their cellular structure was investigated by varying material and process parameters: molar mass of the FEP, the magnitude of the pressure drop and the temperature during the foaming process. The elastic modulus showed a strong influence of the cellular structure of the films. A decrease of the molar mass of FEP as well as an increase of pressure drop and foaming temperature considerably reduced the elastic modulus of the foams generated. This lowering of the stiffness correlated with the decrease of foam density. In addition, a significant contribution of the cellular morphology and the thickness of the compact skin layers of the foams could be noted. A further reduction of the foam stiffness was achieved by a biaxial stretching of the foams, which deformed the cells into a lens shape.
WW1::864

Conductivity and adhesion enhancement in low-temperature processed indium tin oxide/polymer nanocomposites - Maksimenko, Ilja; Groß, Michael; Königer, Tobias; Münstedt, Helmut; Wellmann, Peter (Thin Solid Films, 2010)
We report on the conductivity and adhesion enhancement of indium tin oxide (In(2)O(3):Sn; ITO) nanoparticle films by the application of polymers as matrix material. We fabricated ITO layers at a maximum process temperature of 130 degrees C by modifying and spin-coating nanoparticulate ITO dispersions. Dispersions containing the organic film-forming agent polyvinylpyrrolidone (PVP) and the organofunctional coupling agent 3-methacryloxypropyltrimethoxysilane (MPTS) have been developed to obtain transparent and conducting coatings on substrates which do not withstand high process temperatures like polymers or already processed glasses. The layers were cured by UV-irradiation as well as by low-temperature heat treatment (T = 130 degrees C) in air and under forming gas atmosphere (N(2)/H(2)). The influence of the additives on the electrical, optical, morphological and mechanical layer properties is reported. Compared to best pure ITO layers (3.1 Omega(-1)cm(-1)), the ITO-MPTS-PVP nanocomposite coatings exhibit a conductance of 9.8 Omega(-1)cm(-1). Stable sheet resistances of 750 Omega/square at a coexistent transmittance of 86% at 550 nm for a layer thickness of about 1.3 mu m were achieved. The conductance enhancement is a consequence of the consolidation of the ITO nanoparticle network due to the acting shrinkage forces caused either by drying in the case of PVP or UV-irradiation induced condensation and polymerization reactions in the case of MPTS. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide (ITO); Nanoparticles; Polyvinylpyrrolidone (PVP); 3-Methacryloxypropyltrimethoxysilane (MPTS); Nanocomposite; Adhesion

Conductivity of polymethylmethacrylate filled with carbon black or carbon fibres under oscillatory shear - Krückel, Johannes; Stary, Zdenek; Triebel, Christian; Schubert, Dirk W.; Münstedt, Helmut (Polymer, 2012)
The electrical conductivity of polymer composites containing conductive fillers is strongly influenced by the structure of the particle network. Therefore, the change of this network under deformation in the molten state is of great interest, in order to obtain materials with desirable electrical properties. In this work polymethylmethacrylate containing carbon black or carbon fibres was exposed to oscillatory shear deformations and the electrical conductivity of the materials was measured simultaneously. It was found that the particle networks in the composites filled with carbon fibres were more sensitive to deformation than those of the carbon black composites. The stability of the networks increased with growing amount of fillers. Furthermore, it could be shown that conductive and rheological networks behave completely different under shear deformations.
Keywords: Polymer composites; Rheology; Conductivity

Continuous direct melt foaming of a preceramic polymer using carbon dioxide: extrusion device and first results - Wolff, Friedrich; Münstedt, Helmut (Journal of Materials Science, 2011)
EAM Import::2019-03-13

Determination of method-invariant activation energies of long-chain branched low-density polyethylenes - Keßner, Ute; Kaschta, Joachim; Münstedt, Helmut (Journal of Rheology, 2009)
The idea to use the temperature dependence of rheological properties, especially the flow activation energy, as a tool to investigate branching structures is well-known from literature. However, there is no common method to obtain activation energies, which are independent of the measuring quantity chosen, particularly, in the case of slightly thermorheologically complex polymers like low-density polyethylene (LDPE). Hence, differing activation energies result, which cannot unequivocally be correlated with the branching structure. This paper describes a method for the determination of method-independent activation energies for thermorheologically complex polymers like LDPE. From a generalized approach to the time-temperature superposition principle, a vertical shift factor is introduced, which is related to the temperature dependence of the linear steady-state compliance. In the case of the complex LDPE, a decrease in the linear steady-state compliance with temperature is found. Taking this experimentally determined shift factor into account leads to activation energies independent of the rheological quantity chosen. These values can be taken to analyze differences of the branching architecture.
Keywords: polymer melts; rheology; viscoelasticity

Effects of Bioglass and ß-TCP containing three-dimensional laser sintered polyetheretherketone composites on osteoblasts in vitro - von Wilmowsky, Cornelius; Vairaktaris, Eleftherios; Pohle, Dirk; Rechtenwald, Thomas; Lutz, Rainer; Münstedt, Helmut; Koller, Garrit; Schmidt, Michael; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Nkenke, Emeka (Journal of Biomedical Materials Research Part A, 2007)
LFT Import::2019-07-16 (1422)

Elastic behavior and processing of polymer melts - Münstedt, Helmut (AIP Conference Proceedings, 2019)
Whereas the influence of viscous properties of a polymer melt on some aspects of processing has widely been reported in the literature, investigations with respect to elastic properties are rare. In this paper effects of the elastic behavior on processing and those of processing on molecular orientation and recoverable strain are presented. As elastic property the role of extrudate swell in its many facets is discussed. Experiments on cast film extrusion are described and their results discussed as a function of the Deborah number, which is often used as a quantity for the elasticity at short processing times. Film contours and resonance frequencies are presented in detail. With respect to the influence of processing on properties of manufactured items results from the literature are discussed, which show that one has to distinguish between effects on the orientation of molecule segments and on the recoverable strain. The role of non-uniform distributions of the recoverable strain within a manufactured sample for its properties is shortly addressed.
CRIS-Team Scopus Importer:2019-06-21

Elasticity of polystyrene melts filled with silica nanoparticles: Influence of matrix polydispersity - Triebel, Christian; Kunzelmann, Peter; Schubert, Dirk W.; Münstedt, Helmut (Final Program and Book of Abstracts, 2011)

Elongational experiments on polymer melts and their assessment - Münstedt, Helmut (AIP Conference Proceedings, 2013)
Regarding the literature, steady-state values of the elongational viscosity are not widely documented and it is still an open question, whether the time-dependent elongational viscosity of strain-hardening polymeric materials runs through a maximum as a function of time before it reaches its steady state. For the assessment of molecular theories reliable experimental data are essential, however. From a survey of extensional experiments at constant elongational rates it becomes very probable that an extended stationary state of elongational exists and that maxima of the tensile stresses or even overshoot phenomena are due to non-uniform deformations of the samples. This conclusion is supported by creep experiments for which a steady state is reached at comparatively smaller total elongations corresponding to a better uniformity. © 2013 AIP Publishing LLC.
Created from Fastlane, Scopus look-up
Keywords: Experimental devices; Extensional rheology; Polymer melts; Steady-state elongational viscosity; Theories; Uniformity of deformation

Extensional rheology and processing of polymeric materials - Münstedt, Helmut (International Polymer Processing, 2018)
Many processing operations of polymeric materials are dominated by extensional flow. In this paper the question is addressed in which way rheological data obtained from elongational laboratory experiments can be used to describe the material behavior in various processes. Particularly discussed is the uniformity of geometrical features of items with respect to the strain hardening of the polymeric materials, because uniformity is important for many end-use properties. Convincing correlations with extensional rheology could not be established for thermoforming experiments on polypropylene. However, for blown and drawn films it was found that the uniformity of thickness improved, if strain hardening was introduced. The bubble stability could be related to the melt strength of the sample. Furthermore, the influences of elasticity and strain hardening on the neck-in during drawing of films were elucidated. Moreover, it was shown in which way extensional rheology can be used to assess foaming.
Created from Fastlane, Scopus look-up

Extrusion Foaming of a Preceramic Silicone Resin with a Variety of Profiles and Morphologies - Wolff, Friedrich; Ceron Nicolat, Bruno; Fey, Tobias; Greil, Peter; Münstedt, Helmut (Advanced Engineering Materials, 2012)
Preceramic foams with a variety of profiles and morphologies were fabricated by a continuous foam extrusion process based on a single-screw extruder. A methyl silicone resin was used as the preceramic polymer and carbon dioxide as the foaming agent. Variations of the foam morphology were achieved by changing the key process parameters carbon dioxide content, foaming pressure, and foaming temperature. Samples of different porosities, cell densities, pore sizes, and pore size gradients were obtained. From these results, conditions for the fabrication of particular foam structures can be derived. Various foam profiles as rods, tapes, and tubes were extruded and pyrolysed into ceramic foams.

Flow behavior of polypropylenes with different molecular structures in a coat-hanger die - Grieß, Hans Jürgen; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of the flow behavior of three polypropylene melts with different molecular structures during extrusion through a coat-hanger die is presented. Two linear and one long-chain branched material, rheologically characterized in shear and elongation, were investigated. Using laser-Doppler velocimeter measurements of the velocity profiles across the gap height were performed at five various locations along the die. The uniformity of the velocity distribution along the die has been assessed using the maximum velocities v0 of the corresponding velocity profiles across the gap. The velocity distribution along the die changes with throughput and temperature. Regarding the rheological properties, it was found that the power-law index of the viscosity as a function of shear rate has a decisive influence on the uniformity of flow but that the pronounced strain hardening in elongation typical of the long-chain branched polypropylene is not reflected by the velocity distribution along the die. Copyright © 2012 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up

Foaming of thin films of a fluorinated ethylene propylene copolymer using supercritical carbon dioxide - Zirkel, Larissa; Jakob, Martin; Münstedt, Helmut (Journal of Supercritical Fluids, 2009)
The foaming of films of a fluorinated ethylene propylene copolymer (FEP) using supercritical carbon dioxide (scCO_2) was investigated. For this purpose, a one-step foaming process was applied to the films inside a pressure vessel at temperatures in excess of 200 °C and pressures up to 30 MPa. The films prepared show a homogeneous cellular structure with thin compact polymer layers on both sides. The foaming behaviour of the FEP films is determined in dependence on the exposure time of the polymer to the scCO_2, the processing temperature and pressure as well as on the pressure drop rate during the foaming process. The resulting density and the foam morphology can be related to the pressure level during the saturation process. The size of the cells generated mainly depends on the foaming temperature, whereas their number per volume is determined by the magnitude of the applied pressure. Furthermore, the pressure drop rate influences the size of the cells in a way that significantly fewer but larger bubbles are found for longer times of depressurizing. This finding can be explained by nucleation rates becoming the smaller the slower the rate of pressure decrease.
EAM Import::2019-03-14

Gelation of polyvinylbutyral solutions by the addition of tetrabutyl orthotitanate - Wegener, Carsten Moritz; Kaschta, Joachim; Münstedt, Helmut; Roosen, Andreas (Rheologica Acta, 2014)
This paper discusses the gelation of polyvinylbutyral (PVB) solutions by the addition of tetrabutyl orthotitanate. The addition of around 0.10 vol.% tetrabutyl orthotitanate to an ethanol-based PVB solution already causes a pronounced gelation. For the characterization of this gelation reaction, different rheological measurements are used. The characterization is mainly performed in the linear viscoelastic regime. Time sweeps prove the stability of the samples during the measuring time. Frequency sweeps are used to investigate the state of gelation after different reaction times as well as the dependence of the degree of the gelation on the tetrabutyl orthotitanate concentration. Furthermore, the gelation point is determined by measuring the loss factor tan delta as a function of frequency. A strong influence of water on the degree of gelation is shown; by the addition of different amounts of water, the gelation can be controlled or even avoided. Amplitude sweeps reveal the breakdown of certain network structures at high amplitudes which recover after the strain is lowered.
Keywords: Polyvinylbutyral (PVB); Gelation with titanate; Dynamic mechanical analysis (DMA); Network characterization; Gel point

Graded Cellular Ceramics from Continuous Foam Extrusion - Ceron Nicolat, Bruno; Wolff, Friedrich; Dakkouri, Andrea S.; Fey, Tobias; Münstedt, Helmut; Greil, Peter (Advanced Engineering Materials, 2012)
Cylindrical SiOC foam filaments with a radial gradient in pore cell size were processed by continuous extrusion foaming of a methyl polysilsesquioxane. Upon leaving the extrusion nozzle foaming was initiated by pressure release which caused precipitation of supersaturated carbon dioxide from the polymer filament. Rapid cooling of the thin filaments generates a radial gradient of melt viscosity which gives rise for formation of closed cell morphology of isotropic pore cells in the core (diameter?<!–?200?mu m) and non-isotropic pore cells near the sur-face (shell; <20?mu m). After pyrolysis at temperatures ranging from 800 to 1400?degrees C the stabilized polymer gradient foams were converted into closed cell SiOC ceramic gradient foams. XRD reveals the SiOC residue to be amorphous up to 1200?degrees C whereas crystallization of beta-SiC was observed at 1400?degrees C. A superior compressive strength of 9?MPa and a Young's modulus of 7?GPa at a relative density of 0.18 were measured at an optimum pyrolysis temperature of 1000?degrees C.–>
Keywords: carbon dioxide foaming; graded porosity; polymer derived cellular ceramics

Influence of a compatibilizer on the morphology development in polymer blends under elongation - Stary, Zdenek; Pemsel, Thomas; Baldrian, Josef; Münstedt, Helmut (Polymer, 2012)
Compatibilization is the modification of the interface in immiscible polymer blends in order to refine and stabilize their phase structure. The presence of a compatibilizer at the interface markedly affects the deformation behaviour of the dispersed droplets during and after cessation of flow. In this work the morphology development in blends of polystyrene and linear low-density polyethylene compatibilized with styrene-butadiene-styrene triblock copolymer during and after uniaxial elongation was investigated by means of electron microscopy and small-angle X-ray scattering. The incorporation of only 1 wt.-% of the compatibilizer led to a pronounced increase of the stationary elongational viscosity of the blend. It was found, that at moderate capillary number (Ca ≈ CaCR) the compatibilizer stabilises the droplets against break-ups during the flow. When Ca >> CaCR no differences in the deformation of uncompatibilized and compatibilized droplets were observed. After cessation of the flow, the presence of the compatibilizer prevented the droplet break-up and supported and accelerated the shape recovery of the elongated particles. © 2012 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Blends; Compatibilization; Morphology

Influence of hydrostatic pressure on rheological properties of polymer melts - A review - Münstedt, Helmut (Journal of Rheology, 2020)
Rheological properties of polymer melts are significantly dependent on molecular structure and external parameters. While numerous experimental data of the dependence of the rheological behavior on stress, shear rate, and temperature are available in the literature, much less is known on the effect of hydrostatic pressure. This article reviews the knowledge about the pressure dependence of rheological properties of polymer melts. The different experimental devices for measurements under pressure are described, and the methods of determining the pressure coefficients of viscosity are critically analyzed. Very few investigations of the pressure dependence of viscoelastic properties are addressed. A comparison of the pressure coefficients of commercial polymers obtained by various authors from viscosity measurements with different methods shows the deficits in getting exact data. It can be said, however, that the pressure coefficients increase in the order of high density polyethylene, linear low-density polyethylene, low-density polyethylene, polypropylene, and polystyrene. For amorphous polymers and, particularly, for polystyrene, it is shown how the pressure coefficients decrease with growing temperature. For polyolefins, this dependency is less significant. The free volume concept is discussed with respect to an interpretation of the experimental findings. Results of using the hole fraction theory for describing the pressure dependence of viscosity are presented and critically assessed.
CRIS-Team Scopus Importer:2020-04-28

Influence of matrix polydispersity on the viscoelastic properties of polystyrene melts filled with nano silica - Triebel, Christian; Kunzelmann, Peter; Schubert, Dirk W.; Münstedt, Helmut (Book of Abstracts, 2012)

Influence of molar mass distribution and long-chain branching on strain hardening of low density polyethylene - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut; Becker, Florian; Buback, Michael (Rheologica Acta, 2009)
Low-density polyethylenes (LDPE) were synthesized in a laboratory-scale autoclave under high pressure. These samples were found to possess a high molar mass tail, resulting in a distinctly bimodal molar mass distribution and a lower concentration of long-chain branching than typical of commercial LDPEs. Rheological experiments in elongation showed that these samples exhibit a very pronounced strain hardening, which could be favorable for distinct processing operations. Although the samples have a rather high molar mass (M(w) = 2...4 x 10(6) g/mol), their zero shear-rate viscosities eta(0) and their shear thinning behavior are still in a range, where thermoplastic processing is possible. Aqualitative understanding of the experimental results is tried by the model of the Cayley tree.
Keywords: Low-density polyethylene; Autoclave process; Molar mass distribution; Long-chain branching; Elongational rheology; Viscosity functions

Influence of molecular parameters on the stress dependence of viscous and elastic properties of polypropylene melts in shear - Resch, Julia; Kaschta, Joachim; Wolff, Friedrich; Münstedt, Helmut (Rheologica Acta, 2011)
The stress dependencies of the steady-state viscosity eta and, particularly, that of the steady-state elastic compliance J(e) of various linear isotactic polypropylenes (PP) and one long-chain branched PP are investigated using creep-recovery tests. The creep stresses applied range from 2 to 10,000 Pa. In order to discuss the stress-dependent viscosity eta and elastic compliance J(e) with respect to the influence of the weight average molar mass M-w and the polydispersity factor M-w/M-n the PP are characterized by SEC-MALLS. For the linear PP, linear steady-state elastic compliances J(e)(0) in the range of 10(-5)-10(-3) Pa-1 are obtained depending on the molar mass distribution. J(e)(0) of the LCB-PP is distinctly higher and comes to lie at around 10(-2) Pa-1. J(e)(0) is found to be independent of M-w but strongly dependent on polydispersity. eta and J(e) decrease with increasing stress. For the linear PP, J(e) as a function of the stress tau is temperature independent. The higher M-w/M-n the stronger is the shear thinning of eta and the more pronounced is the stress dependence of J(e). For the LCB-PP, the strongest stress dependence of eta and J(e) is observed. Furthermore, for all PP J(e) reacts more sensitively to an increasing stress than eta. A qualitative explanation for the stronger stress dependence of J(e) compared to eta is given by analyzing the contribution of long relaxation times to the viscosity and elasticity.
Keywords: Polypropylene; Viscosity; Steady-state elastic compliance; Stress dependence; Molecular structure

Influence of various pretreatments on molecular and rheological properties of a linear and a long-chain branched polypropylene - Münstedt, Helmut; Kaschta, Joachim (Rheologica Acta, 2024)
The influence of a mechanical or a thermal pretreatment of a linear (L-PP) and a long-chain branched polypropylene (LCB-PP) in the molten state was studied. The molar mass distributions and the branching structure were determined by high-temperature gel permeation chromatography HT-GPC coupled with laser-light scattering. The samples were extruded through long or short capillaries of various geometries corresponding to a predominant shear or elongational deformation. As a rheological probe, the extrudate swell at low stresses was measured for the differently pretreated samples. For the L-PP, neither molecular nor rheological changes were observed. However, the extrudate swell of the LCB-PP was found to decrease with increasing volume throughput. It was more strongly affected by shear in the capillary than by molecule stretching in the entry region. The smaller extrudate swell was accompanied by a decrease of the high molar mass tail of the LCB-PP, which could be the reason for the decay of swell, in principle. However, a comparable degradation of the high molar mass tail was obtained by a pure thermal treatment that was shown to leave the extrudate swell unchanged. This result and the unaffected branching structures found by high-temperature gel permeation chromatography (HT-GPC) support the hypothesis of a change of the branching topography by the mechanical pretreatment.<br

Investigations of slip in capillary flow by laser-Doppler velocimetry and their relations to melt fracture - Münstedt, Helmut (AIP Conference Proceedings, 2015)
Flow profiles within a slit capillary are measured by laser-Doppler velocimetry. They allow the direct determination of the slip velocity at the wall. It is demonstrated that the flow profile of the melt of a high density polyethylene (HDPE) already shows slip components at small shear rates. At high shear rates the slip is dominant and a plug flow is found. Furthermore, it is shown that the surface irregularity called "shark skin" is generated at the slit exit by the stretching of surface layers at pronounced elongational rates. These elongational rates are due to the differences between the flow velocities at the wall of the slit and those of the extruded strand. It is shown how "shark skin" may be avoided when the elongational rate is reduced by introducing slip of the melt in the slit using special additives.
Created from Fastlane, Scopus look-up

In vivo evaluation of B-TCP containing 3D laser sintered poly(ether ether ketone) composites in pigs - von Wilmowsky, Cornelius; Lutz, Rainer; Meisel, Ulf; Srour, Safwan; Rupprecht, Stephan; Toyoshima, Takeshi; Nkenke, Emeka; Schlegel, Karl Andreas; Pohle, Dirk; Münstedt, Helmut; Rechtenwald, Thomas; Schmidt, Michael (Journal of Bioactive and Compatible Polymers, 2009)
The aim of this study was to produce an individually shaped medical implant from a 3D database and to evaluate the biological behavior of a laser sintered poly(ether ether ketone) (PEEK) implant with incorporated osteoconductive bone materials in porcine bone defects. Laser sintered PEEK samples containing ß-tricalciumphosphate (ß-TCP) were implanted into critical size defects in the frontal skull of ten pigs. Compression moulded pure PEEK was used as a reference material. The bone-implant interface was histomorphometrically analysed after 6, 12, and 24 weeks. Histomorphometrical evaluations after 24 weeks revealed that the superficially located ß-TCP was in contact with the surrounding bone, whereas the other groups were fibrous encapsulated. Interfacial shear strength was significantly higher for the ß-TCP containing group in comparison to the compression moulded PEEK group (p = 0.004) and the laser sintered PEEK group. The laser sintered PEEK implants seem to be attractive as bone substitutes for reconstructive surgery due to their individually constructed 3D shape and biocompatibility. © 2009 SAGE Publications.
Created from Fastlane, Scopus look-up
Keywords: ß-TCP; 3D shaped implants; Bone reconstruction.; Bone substitution; In vivo; Individually shaped implants; Laser sintering; Poly(ether ether ketone) (PEEK); Sintered PEEK biocompatibility; Tissue engineering

Is electrical percolation in carbon-filled polymers reflected by rheological properties? - Münstedt, Helmut; Stary, Zdenek (Polymer, 2016)
It is well known that the electrical conductivity of particle filled polymers exhibits a distinct percolation behavior. In the literature it is stated that this percolation is accompanied by a comparable change of rheological properties designated "rheological percolation". Evaluating dynamic-mechanical measurements from the literature and using own results from creep experiments on polymethylmethacrylate melts filled with graphite it is demonstrated that rheological properties change continuously as a function of particle concentration in the range of the threshold of electrical conductivity. A model is proposed and discussed, which describes the electrical and rheological properties. For rendering a polymer conductive, continuous pathways of conducting fillers are necessary. The rheological behavior in the percolation regime is determined by matrix molecules that become hindered in their mobility by an attachment to the particles.
Created from Fastlane, Scopus look-up
Keywords: Composites; Electrical conductivity; Rheological properties

Materialspezifische Vorraussetzung für das Lasersintern von Polyetheretherketonen als Knochenersatz für den Schädelbereich - Pohle, Dirk; Rechtenwald, T.; von Wilmowsky, Cornelius; Neukam, Friedrich Wilhelm; Münstedt, Helmut (BIOmaterialien, 2007)
LFT Import::2019-07-16 (1427)

Mechanical pretreatment of polymer melts: Critical aspects and new rheological investigations on a linear and a long-chain branched polypropylene - Münstedt, Helmut (Journal of Rheology, 2021)
It has been known for some time that mechanical pretreatments of melts of long-chain branched polymers can increase the melt index and reduce the extrudate swell. This effect is not due to changes of the molar mass, its distribution, or the degree of branching because it may be reversed by long-term annealing or dissolution of the polymeric material and subsequent precipitation. Furthermore, molecular analysis shows a molecular structure unaltered by the treatment. The effect has not been completely understood up to now, and it is still an open question as to whether it is restricted to long-chain branched polymers, which have been preferably studied. This paper gives an overview of results from the literature and presents comparable measurements on a well characterized long-chain branched and a linear polypropylene. A wide range of linear and nonlinear rheological properties were studied, and it became obvious that long-chain branching is a strong structural precondition for the pronounced pretreatment effect occurring in processing. Based on this result, models from the literature are discussed, and it is found that chain alignment may qualitatively explain the rheological measurements.
CRIS-Team Scopus Importer:2021-07-16

Melt strain hardening of polymeric systems filled with solid particles: review and supplementary experimental results - Münstedt, Helmut (Rheologica Acta, 2024)
Melt strain hardening is an interesting characteristic property of the elongational flow of polymers. While strain hardening of many unmodified polymer melts has been widely discussed, a comprehensive presentation of the influence of particles on this property is missing. Using literature data and own measurements, the effects of solid particles of various geometries are compared. Micro-sized particles generally reduce melt strain hardening and may even lead to strain thinning. This behavior is postulated to be due to shear flow components around the particles and resulting shear thinning of the polymer matrices that reduces the resistance to flow. More complex is the influence of nano-sized fillers and layered silicate nanoparticles, in particular. Weakly exfoliated particles show effects similar to micro-fillers, but for strongly exfoliated silicates distinct strain hardening is observed that increases with decreasing elongational rate. This behavior is particularly pronounced for polymers modified with maleic anhydrides and thought to be related to electrostatic forces between exfoliated platelets of the silicates and polymer molecules hindering molecular motions.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Filler-polymer interactions; Melt strain hardening; Polymer melts; Rate dependence; Solid fillers

Melt strain hardening of polymeric systems increasing with decreasing elongational rate: Experimental results and discussion of models - Münstedt, Helmut (Physics of Fluids, 2024)
Melt strain hardening is a special feature of polymer materials and polymeric systems relevant for applications and fundamental insights into rheological properties. Strain hardening is dependent on the molecular structure of materials and deformation parameters. This paper deals with literature results of materials exhibiting strain hardening increasing with decreasing elongational rate opposite to most of common polymers. Such a behavior is found for ionomers and polymers with hydrogen bonding, and electrostatic molecular interactions are discussed as the physical origin. Furthermore, layered composites of non-strain hardening polymers are presented that can be rendered strain hardening by introducing compatibilizers or increasing the effect of interfacial tension between two layers by using multilayer arrangements. The strain hardening behavior of polypropylene/high density polyethylene blends of various compositions is discussed. Measurements on ethylene/α-olefin copolymers showing strain hardening significantly increasing with decreasing rate in contrast to linear ethylene homopolymers are described, and it is hypothesized that this behavior is due to a heterogeneous molecular structure with large differences of molar masses of the components.
CRIS-Team Scopus Importer:2025-02-04

Molecular structure and rheological properties of a poly(ethylene terephthalate) modified by two different chain extenders - Härth, Michael; Dörnhöfer, Andrea; Kaschta, Joachim; Münstedt, Helmut; Schubert, Dirk W. (Journal of Applied Polymer Science, 2020)
This paper compares the molecular structure and rheological properties of a commercial poly(ethylene terephthalate) (PET) after reactive processing with different concentrations of either pyromellitic dianhydride (PMDA) or a multifunctional epoxide (Joncryl®ADR‐4368) as a chain extender. By size exclusion chromatography with triple detection, an increase of molar mass, a broadening of molar mass distribution, and the generation of long‐chain branched molecules were found for both chain extenders. While gel‐free materials were obtained with PMDA, the processing with Joncryl leads to the formation of gels. The effect of branching, indicated by the Mark–Houwink exponent, is more pronounced for materials with Joncryl compared to PMDA and points to a more compact branching structure of the PET/Joncryl molecules. Rheological measurements in shear and elongation support the analysis from SEC and reveal a complex tree‐like branching structure for both chain extenders. In addition, the role of the two modifiers with respect to processing was assessed.<br

On the viscosity maximum during uniaxial extension: Material property or measuring artifact? - Stary, Zdenek; Burghelea, Teodor; Münstedt, Helmut (AIP Conference Proceedings, 2013)
An experimental investigation of the viscosity maximum observed during uniaxial extension of a low density polyethylene is presented. For this purpose, traditional integral viscosity measurements on a Münstedt-type extensional rheometer are combined with local measurements based on the in-situ visualization of the sample under extension. For elongational experiments at intermediate constant strain rates local maximum of the extensional viscosity is systematically observed. Images of samples within this regime show that secondary necks develop along the sample at the moment when the maximum of the integral viscosity is observed. The emergence of a maximum of the integral elongational viscosity is, thus, related to the distinct non-uniformity of deformation states and most probably not to the rheological properties of the material. Moreover, the position of the viscosity maximum was found to be dependent on the initial geometry of the specimen. This indicates again that the appearance of the transient viscosity maximum is not a material property but an artifact caused by a geometrical non-uniformity of highly stretched specimens. © 2013 AIP Publishing LLC.
Created from Fastlane, Scopus look-up
Keywords: Elongational flow; Polymer melts; Rheology

Physical foaming of fluorinated ethylene-propylene (FEP) copolymers in supercritical carbon dioxide: single-film fluoropolymer piezoelectrets - Voronina, O.; Wegener, Michael; Wirges, Werner; Gerhard, Reimund; Zirkel, Larissa; Münstedt, Helmut (Applied Physics A-Materials Science & Processing, 2008)
Cellular polymer foams with significant piezoelectric activity were prepared from fluorinated ethylene-propylene (FEP) copolymers. The required void structure is obtained by saturation of FEP films with supercritical carbon dioxide and a subsequent heat treatment for controlled inflation. After bipolar electric charging of the voids and evaporation of electrodes, the FEP films show piezoelectric d33 coefficients up to 50 pC N. The present physical foaming process generates cellular efficients up to 50 pC/N. The present physical foaming process generates cellular fluoropolymer piezoelectret films with usually only one single void across the film thickness.
EAM Import::2019-03-12

Polyurethane/silver-nanocomposites with enhanced silver ion release using multifunctional invertible polyesters - Peukert, Wolfgang; Damm, Cornelia; Triebel, Christian; Vasylyev, Serhiy; Stara, Hana; Özpinar, Celal; Münstedt, Helmut; Hausmann, Sebastian (Journal of Materials Chemistry, 2011)
Nano-silver composites with a thermoplastic polyurethane as the matrix were prepared by two different routes. Using the so-called in situ preparation, silver nanoparticles were obtained by a thermal reduction of silver acetate during melt mixing. In addition, a more sophisticated ex situ preparation method was developed. Here, the silver nanoparticles are synthesized in an invertible polyester resulting in much smaller particle sizes. The particles obtained are surrounded by the polyester cage, which stabilizes them with respect to agglomeration. Hence, an incorporation of those particles into a polymer melt with common techniques like extrusion leads to an even distribution. This is due to the fact that the invertible polyester and the polymer matrix are entirely miscible which was proven with DSC measurements. The silver ion release of the composites prepared was measured with anodic stripping voltammetry. At a constant weight percentage of silver in the polymer, the composite with the ex situ silver nanoparticles exhibits a silver ion release which is about two orders of magnitude higher than the release from the composite with the in situ silver nanoparticles. This observation is explained by the higher specific surface area of the smaller particles and a higher coefficient of diffusion for silver ions. A concentration of only 0.07 wt% silver nanoparticles, prepared with the ex situ method, exhibits a high enough release of silver ions to achieve antimicrobial properties. © 2011 The Royal Society of Chemistry.
Keywords: nanoparticle; polymer; thermal; reduction; ex-situ

Prediction of steady-state viscous and elastic properties of polyolefin melts in shear and elongation - Rolón-Garrido, Víctor; Resch, Julia; Wolff, Friedrich; Kaschta, Joachim; Münstedt, Helmut; Wagner, Manfred (Rheologica Acta, 2011)
The linear and nonlinear steady-state viscosities and elastic compliances were measured in shear and elongational flows for two low-density polyethylenes, a linear polypropylene, and two metallocene catalyzed polyethylenes (one linear and one long-chain branched) by Wolff et al. (Rheol Acta 49:95-103, 2010) and Resch (dissertation, 2010). Comprehensive data of this type are rarely found in the literature, and comprehensive modeling of both viscous and elastic effects is even rarer. In this contribution, the reliability of a modeling approach proposed by Laun (J Rheol 30(3):459-501, 1986) and based on the damping function concept is tested. The strain hardening seen for the long-chain branched polymers and its absence in the case of the linear polymer, the stronger decrease of the tensile compliance in comparison to the shear compliance with increasing stress, as well as the extended linear-viscoelastic regime of the shear viscosity in contrast to the shear compliance are correctly modeled. While the modeling of the nonlinear response in shear can be achieved with only one material parameter for most of the polymers considered here, the nonlinear modeling in elongation is achieved with two parameters. The same parameter values are shown to describe viscous as well as elastic properties of the melts, and thus the relations of Laun can be used to test the consistency of viscosity and compliance measurements.
Keywords: Rheology; Creep experiments; Shear flow; Elongational flow; Damping function; Strain hardening; Low-density polyethylene; Polymer melts

Recoverable extensional flow of polymer melts and its relevance for processing - Münstedt, Helmut (Polymers, 2020)
While the uniaxial elongational viscosity is widely investigated, and its relevance for processing is described in the literature, much less has been published on the recoverable extensional flow of polymer melts. This paper presents a short overview of the dependencies of the recoverable elongation on the molecular structure of a polymer, and on some experimental parameters. Its main focus lies on the discussion of processing operations and applications that are largely affected by the elastic components of elongational flow. The recoverable portions of stretched films are considered, and the exploitation of the shrinkage of films, due to the recovery of frozen recoverable deformations, and its role for applications are addressed. The analysis of measurements of velocity fields in the entry region of a slit die and results on the determination of the recoverable elongation from uniaxial experiments, according to the literature, lead to the conclusion of dominant elastic extensions. Considering these facts, the assumptions for Cogswell's widely used method of determining elongational viscosities under processing conditions from entrance flow are not realistic. As examples of a direct application of extrudate swell from short dies for processing, pelletizing and fused deposition modelling within additive manufacturing are addressed. The special features of extrudate swell from short dies, and uniaxial recoverable elongation for a polymer filled with rigid particles in comparison to an immiscible polymer blend, are presented and discussed.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Entrance flow; Extrudate swell; Extrusion processes; Filled polymers; Polymer blends; Polymer melts; Recoverable elongation; Short dies; Shrink films

Rheological experiments at constant stress as efficient method to characterize polymeric materials - Münstedt, Helmut (Journal of Rheology, 2014)
Rheology has achieved a strong position for the characterization of polymeric materials during the last 40 years. Dynamic-mechanical measurements are widely used for this purpose. On several examples, this paper demonstrates the potential of creep-recovery whose application has still been rather limited. In many cases, dynamic-mechanical experiments suffer from the fact that for several reasons, the angular frequencies applied are not chosen low enough to reach the terminal regime for which relationships between rheological quantities and molecular parameters have been established. In creep and a subsequent recovery, the time scales can be extended into the stationary regime in the linear range of deformation, and therefore, creep recovery is an efficient method to directly determine the zero-shear viscosity η0 and the linear steady-state recoverable compliance Je0. For a polymer melt with long relaxation times, it is shown how time-dependent creep data converted into dynamic-mechanical quantities can be used to extend the frequency scale to the terminal regime. The power of Je0 and its temperature dependence is demonstrated for the analysis of the branching structure of a polymer. Furthermore, from such kind of measurements, interesting insights into the interactions between particles and matrix molecules in filled polymeric materials were obtained. As shown in elongational experiments, the steady state of deformation at a constant stress is reached at shorter times than at the corresponding constant strain rate. The experimental consequences are discussed. Another interesting aspect of creep is that a constant stress implies a constant capillary number. The advantage of this experimental condition for investigations of the droplet deformation in polymer blends is demonstrated. © 2014 The Society of Rheology.
Created from Fastlane, Scopus look-up

Rheological measurements and structural analysis of polymeric materials - Münstedt, Helmut (Polymers, 2021)
Rheological measurements of polymer melts are widely used for quality control and the optimization of processing. Another interesting field of rheology is to provide information about molecular parameters of polymers and the structure build-up in heterogeneous polymeric systems. This paper gives an overview of the influence of molar mass, molar mass distribution and long-chain branching on various rheological characteristics and describes the analytical power following from established relations. With respect to applications, we discuss how rheological measurements can be used to gain insight into the thermal stability of a material. A special impact lies in the demonstration, how long-chain branching can be analyzed using rheological means like the zero-shear viscosity as a function of molar mass and strain hardening occurring in elongation. For contributions to branching analysis, the thermorheological behavior and activation energies are particularly discussed. The use of elastic quantities in the case of mechanical pretreatment effects is briefly addressed. The influence of fillers on recoverable properties in the linear range of deformation is analyzed and the role of their specific surface area for interactions described. It is shown how the fundamental results can be applied to study the state of nanoparticle dispersions obtained under special conditions. Furthermore, it is demonstrated that the findings on polymer/filler systems are the base of structure analyses in heterogeneous polymeric materials like polyvinylchloride (PVC) and acrylonitrile-butadiene-styrene copolymers (ABS).
CRIS-Team Scopus Importer:2021-04-23
Keywords: Analysis of branching content; Mechanical pretreatment effect; Particle-filled polymeric systems; Polymer melts; Relations with molecular parameters; Rheological behavior of heterogeneous polymers; Rheological properties; Studies of thermal stability

Rheological properties of conductive polymer composites around the electrical percolation threshold - Stary, Zdenek; Münstedt, Helmut (AIP Conference Proceedings, 2017)
The electrical conductivity of polymeric materials containing conductive particles shows a typical percolation behavior. Besides this effect adding the particles to a polymer matrix affects the rheological properties considerably. In the literature one can find some studies relating the electrical percolation to a comparable change of rheological quantities. The term "rheological percolation" is introduced; however, its definition is not consistent in the literature. In this contribution some literature data obtained from dynamic-mechanical measurements are discussed and confronted with own data from oscillatory and creep-recovery measurements. From a critical evaluation of the data it follows that rheological properties change continuously with the filler content in the range of the electrical percolation threshold. A simple model is proposed to explain the differences between the electrical and rheological behavior of polymer composites.
Created from Fastlane, Scopus look-up

Rheological properties of electron beam-irradiated polypropylenes with different molar masses - Auhl, Dietmar; Stadler, Florian; Münstedt, Helmut (Rheologica Acta, 2012)
Electron beam-irradiated polypropylene undergoes chain scission initiated by the loss of a proton. The resulting macroradicals can lead to branched molecules. However, the understanding of the influence of irradiation on the branching of polypropylene is still scarce. Therefore, this paper investigates structure-property relationships in such irradiated polymers. In general, irradiation yields long-chain branches, which develop from a star-like into a tree-like branching architecture with increasing dose. These conclusions can be drawn from the relation between the zero shear-rate viscosity η 0 and the weight average molar mass M w as well as from the elongational behavior. © 2012 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: Electron beam irradiation; Elongational rheology; Long-chain branching; Polypropylene; Zero shear-rate viscosity

Simultaneous Biaxial Stretching of Polypropylene Resins of Varying Tacticity Part II: Film Morphology and Properties - Capt, L.; Rettenberger, Stefan; Münstedt, Helmut; Kamal, M. R. (International Polymer Processing, 2022)
The simultaneous biaxial stretching behavior of three Ziegler-Natta-based isotactic polypropylene resins of varying isotacticity was studied using a laboratory film stretcher that simulates closely stretching conditions encountered in the commercial process. The effect of isotacticity on the final morphology and end film properties was associated with the effect of isotacticity on the thermal properties of the resin. The results showed that the degree of undermelting, oT(um) = T-m-T, determines the phase composition of the polymer before stretching and the morphology and orientation of the stretched films. The size and orientation of the crystallites in the stretching plane is mostly determined by the degree of undermelting. The elongation at break was correlated with the residual crystallinity of the film before stretching, and the elastic modulus was correlated with the final degree of crystallinity and the density of tie chains.
CRIS-Team WoS Importer:2022-03-25

Steady states in extensional flow of strain hardening polymer melts and the uncertainties of their determination - Münstedt, Helmut; Stary, Zdenek (Journal of Rheology, 2013)
The existence of a plateau, a maximum or even an overshoot of the elongational viscosity of polymer melts as a function of time or extension, respectively, is a hot topic of scientific discussions. Although not essential for the relation of elongational properties to applications, the feature is crucial for a verification of various theories. From a critical review of sophisticated comparative stressing and creep experiments on a low density polyethylene (LDPE), the existence of a pronounced stationary elongational viscosity becomes very probable. These conclusions are supported by investigations on a long-chain branched polypropylene. For an LDPE of higher molar mass with stress maxima caused by local necking within the sample, the maximum viscosities agree with the corresponding steady-state viscosities obtained from creep experiments performed by the same rheometer. The decisive role of the uniformity of the sample deformation for the accuracy of elongational experiments is pointed out. From the findings presented, it becomes evident that a careful control of the sample uniformity is the basic condition for a critical assessment of differing results from the various experimental methods found in the literature. © 2013 The Society of Rheology.
Created from Fastlane, Scopus look-up
Keywords: Elongation; Polymer melts; Sample uniformity; Steady state; Viscosity maximum

Strain hardening of various polymer melts - Münstedt, Helmut (AIP Conference Proceedings, 2023)
Various strain-hardening features of polymer melts in uniaxial extension are described. Of special interest is the dependence of strain hardening on elongational rate. Long-chain branched polyethylene, commercial polystyrenes and their blends with high molar mass components exhibit strain hardening becoming more pronounced with increasing strain rate. For linear polypropylenes, strain hardening is not found within the experimental window. Adding a small amount of a linear polyethylene with ultrahigh molar mass (UHMWPE) results in strain hardening increasing with decreasing rate. Rouse times are used to qualitatively interpret the experimental results on polystyrene. The non strain hardening behavior of linear PP and HDPE can be made plausible by the Rouse model. But for a qualitative understanding of the rate dependence of strain hardening of the PP/UHMWPE blend, the existence of a separate phase of the minor component and special deformation processes at the interface with the matrix have to be postulated.
CRIS-Team Scopus Importer:2023-07-21

Surface Modifications of Polyetheretherketone (PEEK): Results from the Literature and Special Studies of Copper-Coated Films - Münstedt, Helmut; Grossmann, Joern (Polymers, 2022)
For some challenging applications of the high-performance thermoplastic polyetheretherketone (PEEK) in engineering or medical fields, the bonding to other materials is important. In these cases, modifications of the inert polymer surface are often necessary. Results from the literature with respect to sandblasting, corona discharge, plasma treatment, excimer-laser irradiation, and chromium-sulfuric-acid etching are described and discussed. Our own detailed studies of these methods under well-defined experimental conditions are reported, which make their comparability possible and support the assessment for certain applications. PEEK films coated with copper are of special interest due to their potential for flexible electronics. Copper foils glued by an epoxy resin and copper layers from physical vapor deposition are compared with respect to their mechanical adhesion. Surface properties were characterized with respect to roughness, contact angle, and oxygen-to-carbon (O/C) ratio. The latter has been found to be the most decisive parameter for good adhesion. It was shown that an enhancement of the O/C ratio can be achieved in several ways. The advantages and disadvantages of the methods applied are discussed under various aspects of applications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: bonding properties; copper layers; polyetheretherketone; surface analysis; surface treatment

Synthesis and Characterization of Novel Ethylene-graft-Ethylene/Propylene Copolymers - Stadler, Florian; Arikan, Burçak; Kaschta, Joachim; Kaminsky, Walter; Münstedt, Helmut (Macromolecules, 2011)
A sequential metallocene-catalyzed synthesis of ethylene/propylene macromers, which are subsequently incorporated into growing polyethylene chains, leads to comb-like polymers. After the synthesis, a Soxhlet extraction ensures the purity of the sample. The GPC-MALLS analysis reveals narrowly distributed samples with a non-negligible degree of branching. The comb polymers show a very high viscosity, which significantly differs from conventional long-chain branched metallocene polyethylenes (LCB-mPE) but is in agreement with findings on comb model polymers. The zeroshear rate viscosity eta(o) lies significantly above the relation between M(w) and eta(o) for linear and for conventional LCB-mPE. The thermorheological behavior is complex and differs from that observed for LCB-mPE but also does not resemble an LDPE-like thermorheological behavior.

Thermorheological behavior of various long-chain branched polyethylenes - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut (Macromolecules, 2008)
To analyze the thermorheological behavior of various polyethylenes, the relaxation spectra were shifted. Not only linear and short-chain branched PE but also the classical high-pressure LDPE were found to be thermorheologically simple, i.e., the activation energy E(a) is independent of the relaxation strength or the relaxation time, respectively. However, for the long-chain branched metallocene catalyzed polyethylenes investigated a significant dependence of the activation energy E(a) on the relaxation time is detected. At shorter relaxation times E(a) is very close to that of linear PE, but it increases with longer times. The lower E(a) values are assumed to be due to linear molecules and the higher ones to different species of long-chain branched molecules. These findings offer the possibility to use the analysis of the thermorheological complexity to get an insight into the branching structure of polyethylenes. For the LCB-mPE investigated, it can be concluded that they are a mixture of linear and long-chain branched chains.

Thermorheological Behavior of Various Short- and Long-Chain Branched Polyethylenes and Their Correlations with the Molecular Structure - Keßner, Ute; Kaschta, Joachim; Stadler, Florian; Le Duff, Cécile; Drooghaag, Xavier; Münstedt, Helmut (Macromolecules, 2010)
This paper deals with the characterization of a broad range of linear polyethylenes (PE) by means of thermorheology. It is demonstrated, in which way the thermorheological behavior can be related to the comonomer type and content of copolymers. In the first part of this paper, well-established analytical and theological methods are applied to distinguish linear and branched samples. The resolution limit of these methods is demonstrated by the investigation of a blend from a linear-low density PE (LLDPE) and a branched low density PE (LDPE). Special attention is paid to nuclear-magnetic resonance (NMR) spectroscopy in order to reliably determine the comonomer type and content of the samples chosen. The main focus of this paper lies on thermorheological investigations and correlations with the molecular structure. The comparatively high sensitivity of such investigations is highlighted: even small amounts of long-chain branches (LCB) are revealed. The activation energy (E(u)) of linear samples increases with growing comonomer length and content, respectively. As such, thermorheology is demonstrated to be an interesting theological "tool" to get an insight into branching structures. Moreover, the experimental effort is relatively small as solely usual dynamic-mechanical experiments at different temperatures are required.

Time- and temperature-dependent crosslinking behaviour of a silicone resin - Wolff, Friedrich; Kugler, Christoph; Münstedt, Helmut (Rheologica Acta, 2012)
The crosslinking behaviour of a silicone resin which is interesting from a technical point of view was investigated by means of rheology. In order to accelerate the crosslinking process, zinc acetylacetonate and aluminium acetylacetonate were applied as latent catalysts. The effect of the type of catalyst, its concentration, and the temperature on crosslinking was determined by isothermal dynamic-mechanical measurements. A radial gradient in crosslinking causes the gel point to be reached earlier at the outer edge of the sample in the rheometer. This radial gradient is averaged when measuring G′ and G''. Therefore, since the physically well-defined state of critical gelation (gel point) could not be obtained from the data, the time at which a distinct crosslinking state is reached was determined by the crossover of the moduli G′ and G''. For this distinguished point, the denotation gelation index GI is introduced. The gelation indices measured at different temperatures follow an Arrhenius-type relationship. Activation energies between 89 and 126 kJ/mol were determined. They were found to be dependent on the type of catalyst used but independent of its concentration. The activation energies of the crosslinking processes enable the calculation of the gelation index at temperatures not measured directly.
EAM Import::2019-03-12

Various features of melt strain hardening of polymeric materials in uniaxial extension and their relation to molecular structure: review of experimental results and their interpretation - Münstedt, Helmut (Rheologica Acta, 2023)
Strain hardening of polymer melts is able to improve the uniformity of items in processing operations with elongational deformation. Of particular interest in this aspect is the dependence of strain hardening on elongational rate. In its first part, the paper presents a review on melt strain hardening obtained in uniaxial extensional experiments. Its dependence on elongational rate is of particular interest insofar as besides non-strain-hardening polymers, strain hardening increasing or decreasing with rate can be found. Results on linear polymers like polystyrene (PS), polypropylene (PP), high-density polyethylene (HDPE), and linear low-density polylethylene (LLDPE) in dependence on molecular parameters are discussed, as well as those of various blends. Particularly interesting are the strain-hardening features of certain HDPEs and LLDPEs, which could be understood by the assumption of a non-homogeneous chemical structure of the samples. Blends of various compositions of a linear and a long-chain branched PP throw light on the complex relation between branching structure and rate dependence of strain hardening. In the second part of the paper, the different strain-hardening behavior of linear polymers is interpreted by assessing the Rouse times as decisive physical quantity. For blends of certain linear species like HDPE and PP and those of linear with long-chain branched polymers, the existence of separate phases in the molten state is postulated. The assumptions are discussed in the light of the various studies on miscibility of linear and branched polyolefins from the literature. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-08-04
Keywords: Dependence on strain rate; Linear and branched polymers; Melt strain hardening; Models; Polymer blends; Uniaxial elongation

Velocity measurements on a polypropylene melt during extrusion through a flat coat-hanger die - Grieß, Hans Jürgen; Burghelea, Teodor; Münstedt, Helmut (Polymer Engineering and Science, 2012)
An experimental investigation of various flow regimes observed during the extrusion of a polypropylene melt through a flat coat-hanger die by laser-Doppler velocimetry (LDV) is presented. LDV measurements of the velocity profiles across the gap of the die at various locations along the die reveal three different extrusion regimes. At small wall shear stresses, the velocity profiles can be fitted by symmetrical curves with the velocities becoming zero at the die walls. These profiles are not uniformly distributed along the die. An increase of the wall shear stress reveals a second flow regime characterized by a uniform distribution of the velocity profiles along the die. As the wall shear stress is increased even further, a third flow regime characterized by wall slip on the glass windows is observed. This flow regime is systematically characterized by measurements of the slip velocities at various temperatures and throughputs. The maximum velocities along the die are taken to assess the uniformity of flow which decisively influences the thickness of the extruded film. By measuring velocity profiles, at different throughput, and temperatures, the conditions for constant velocities along the die were determined. © 2011 Society of Plastics Engineers.
Created from Fastlane, Scopus look-up

Viscoelastic properties of a silicone resin during crosslinking - Wolff, Friedrich; Kugler, Christoph; Münstedt, Helmut (Rheologica Acta, 2011)
Viscoelastic properties of a silicone resin crosslinked at various extents were characterised by means of rheology. The influence of temperature on the viscoelastic properties of the material as-delivered and in a state pre-crosslinked approximately to the gel point has been investigated by dynamic-mechanical measurements. While the glass transition temperature is increased by the crosslinking, no changes of the free volume fraction at Tg and its thermal expansion coefficient were observed. Taking the different glass transition temperatures into account, it could be shown that the corresponding WLF-parameters are the same. Themolar mass and, hence, the viscosity of the material can be increased by a heat treatment. The dependence of the zero shear-rate viscosity on the weight average molar mass indicates that the existence of entanglements of the polymer molecules is not very probable.
EAM Import::2019-03-12